2016
DOI: 10.18632/oncotarget.7004
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of progestin resistance in endometrial precancer/cancer through Nrf2-AKR1C1 pathway

Abstract: Progestin resistance is a main obstacle for endometrial precancer/cancer conservative therapy. Therefore, biomarkers to predict progestin resistance and studies to gain a more detailed understanding of the mechanism are needed. The antioxidant Nrf2-AKR1C1 signal pathway exerts chemopreventive activity. However whether it plays a role in progestin resistance has not been explored. In this study, elevated levels of AKR1C1 and Nrf2 were found in progestin-resistant endometrial epithelia, but not in responsive end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 41 publications
1
41
0
Order By: Relevance
“…Collagen II is generally used to measure the viability of chondrocytes. 26 Moreover, results of our study indicated that the VEGF level was increased in the BMSCs transfected with Pc-DNA PDGF-B. VEGF is widely thought to play a crucial role in creating new blood vessels after injury.…”
Section: Discussionmentioning
confidence: 58%
“…Collagen II is generally used to measure the viability of chondrocytes. 26 Moreover, results of our study indicated that the VEGF level was increased in the BMSCs transfected with Pc-DNA PDGF-B. VEGF is widely thought to play a crucial role in creating new blood vessels after injury.…”
Section: Discussionmentioning
confidence: 58%
“…Also, inhibition of overall protein synthesis was observed in some cell lines derived from leukemia, lung adenocarcinoma, Ehrlich carcinoma, and hepatoma when the concentration of BRU is higher than 500 nM2122. Recently, BRU has been identified as an unique inhibitor of the Nrf2 pathway at nanomolar concentrations without affecting protein synthesis1423, enhancing the anti-tumor efficacy of cisplatin1424. In this study, we identified for the first time that BRU has the capability to inhibit HIF-1 signaling pathway.…”
Section: Discussionmentioning
confidence: 82%
“…This could be due to the absence of those receptors or to progestin resistance. New biomarkers and molecules are being explored to predict progestin resistance, such as Nrf2/AKR1C1 pathways and in situ metabolism and synthesis of estrogen . The absence of association in our meta‐analysis between hormonal receptors and remission rate could also be due to unknown complex mechanisms of progestin resistance.…”
Section: Discussionmentioning
confidence: 89%